Explaining Student Well-Being in the Digital Era: Cognitive Load as a Psychological Mechanism Linking Technostress and Digital Literacy - Azzahra, Nabilla Feylisha; Na'imah, Tri; Abdul Rahman, Mohd Nazri; Anbari, Mahdi; Silawati, Endah (International Journal of Islamic Educational Psychology, 2026)
The increasing use of learning technology has given rise to various psychological problems among students, particularly technostress and limited digital literacy, stemming from the demands of digital assignments and the complexity of learning platforms. These factors can increase cognitive load and disrupt student well-being. This study used a quantitative explanatory design involving 220 students (N = 220) with a mean age of 16 years (SD = 0.73) and was analyzed using the Partial Least Squares–Structural Equation Modeling approach. The results showed that cognitive load partially mediated the influence of technostress and digital literacy on student well-being. Technostress was shown to increase cognitive load and negatively impact student well-being, whereas digital literacy reduced cognitive load and improved student well-being. In addition, cognitive load also negatively affected student well-being. The novelty of this study lies in revealing the psychological mechanism through the mediating role of cognitive load, explaining how technostress and digital literacy simultaneously affect student well-being, and in providing empirical evidence on Muslim high school students, who are still rarely studied in digital literacy research. These findings emphasize the importance of managing technostress and strengthening digital literacy as key strategies in supporting student well-being in Islamic educational settings.